Assessing Teaching Methods to Improve Traffic Education in Ghanaian Pre-Tertiary Schools - Lawer, Emmanuel Kofi; Fosu, Gabriel Obed; Sakyi-Yeboah, Emmanuel; Aninwaa, Matilda (The Indonesian Institute of Science and Technology Research, 2025)
Road traffic accidents are a leading cause of death among young people in Ghana, emphasizing the urgent need for effective traffic education in pre-tertiary schools. This study evaluates the pedagogical strategies employed in teaching traffic education in the Kumasi Metropolis, focusing on the perceptions and experiences of educators and identifying key barriers to implementation. Utilizing a convergent parallel mixed-methods design, data were collected from 114 teachers through surveys combining quantitative and qualitative approaches. The results indicate that traditional lecture-based instruction, although frequently used, is perceived as the least effective in engaging students. In contrast, interactive methods such as role-playing, multimedia presentations, and field trips, though less frequently employed, were rated as significantly more effective in fostering student understanding and engagement. However, challenges such as inadequate resources, curriculum gaps, and limited teacher training hinder effective implementation. The study calls for targeted interventions, including curriculum integration and enhanced teacher support, to optimize traffic education in Ghanaian schools.